2018
DOI: 10.4055/cios.2018.10.4.407
|View full text |Cite
|
Sign up to set email alerts
|

How to Avoid Graft-Tunnel Length Mismatch in Modified Transtibial Technique for Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Graft

Abstract: BackgroundWe conducted this study to determine the optimal length of patellar and tibial bone blocks for the modified transtibial (TT) technique in anterior cruciate ligament (ACL) reconstruction using the bone-patellar tendon-bone (BPTB) graft.MethodsThe current single-center, retrospective study was conducted in a total of 64 patients with an ACL tear who underwent surgery at our medical institution between March 2015 and February 2016. After harvesting the BPTB graft, we measured its length and that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Increasing height has been associated with greater IAL. 2 , 9 A previous study by Ko et al 9 on avoiding BTB allograft mismatch found a strong positive correlation between individual height and intra-articular length of the ACL with in situ measurements during surgery. Another MRI measurement study by Goldstein et al 5 on BTB allograft mismatch reported significantly shorter (3 mm) PTL in women compared with men; however, the mean height per group was not reported and analysis of the reported data suggested shorter height.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Increasing height has been associated with greater IAL. 2 , 9 A previous study by Ko et al 9 on avoiding BTB allograft mismatch found a strong positive correlation between individual height and intra-articular length of the ACL with in situ measurements during surgery. Another MRI measurement study by Goldstein et al 5 on BTB allograft mismatch reported significantly shorter (3 mm) PTL in women compared with men; however, the mean height per group was not reported and analysis of the reported data suggested shorter height.…”
Section: Discussionmentioning
confidence: 94%
“…Increasing height has been associated with greater IAL. 2,9 A previous study by Ko et al 9 on avoiding BTB allograft Example of patellar tendon length, Caton-Deschamps Index (CDI), and intra-articular ACL length measurements performed on T1-weighted sagittal magnetic resonance imaging. Yellow lines refer to parameters measured on MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper involved a single surgeon's review of 64 autologous BTB grafts used during ACL reconstruction where the surgeon would drill the femoral and tibial tunnels (tibial tunnel drilled at 50 degrees) before harvesting the graft. 10 It was not described how it was determined how long the femoral tunnel was drilled but the overall average was 29.2 mm. The length of the tunnels and intra-articular distance was measured and using these 3 measurements, the graft would be harvested according to that length.…”
Section: Discussionmentioning
confidence: 99%
“…One of the closest techniques to Rule 50 was described in 2018 for ACL reconstruction via modified transtibial technique. This paper involved a single surgeon’s review of 64 autologous BTB grafts used during ACL reconstruction where the surgeon would drill the femoral and tibial tunnels (tibial tunnel drilled at 50 degrees) before harvesting the graft 10. It was not described how it was determined how long the femoral tunnel was drilled but the overall average was 29.2 mm.…”
Section: Discussionmentioning
confidence: 99%